If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 17P + 12 = 13 + 6P Reorder the terms: 12 + 17P = 13 + 6P Solving 12 + 17P = 13 + 6P Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-6P' to each side of the equation. 12 + 17P + -6P = 13 + 6P + -6P Combine like terms: 17P + -6P = 11P 12 + 11P = 13 + 6P + -6P Combine like terms: 6P + -6P = 0 12 + 11P = 13 + 0 12 + 11P = 13 Add '-12' to each side of the equation. 12 + -12 + 11P = 13 + -12 Combine like terms: 12 + -12 = 0 0 + 11P = 13 + -12 11P = 13 + -12 Combine like terms: 13 + -12 = 1 11P = 1 Divide each side by '11'. P = 0.09090909091 Simplifying P = 0.09090909091
| (A+6)(3a-y)=0 | | 2(2x-1)-3x=4 | | 3(x^2+6x+5)=0 | | 24=v/4-17 | | -3(n-3)+3(n+2)=16 | | f(x)=8x^3-3x^2-4x+3 | | cos(11)=x/9.1 | | 3(j+7)=20 | | (18/11)÷(6/33) | | (-8/3)(15/4) | | X(x-21)=180 | | Z^2+bz^11=0 | | -Cos^2(x)+2Cos(x)+3=0 | | a^2-12+27=0 | | 2(x+2)-3(x+3)=-6 | | 5n^2+5n-18=0 | | E(x)=122x+131 | | =2.82x^2-12.69x-7.05 | | 2(5-4y)=10-4y | | -34=5y-4 | | -.75(a-3)=7 | | 16a+5=30i-2 | | -26=-2(v+9) | | 3=.5a+6 | | -10(s+4)=55 | | 3a-4=6a-12 | | -5-5/3b=8 | | 5(2l+1)=65 | | 15.327+7.431= | | 9.6=1.6z+48 | | x^3=512*17+1 | | x^3-1=512*17 |